George I. Sánchez : the long fight for Mexican American integration - Blanton, Carlos Kevin, 1970- (Lamar series in western history., 2015)
"George I. Sánchez was a reformer, activist, and intellectual, and one of the most influential members of the 'Mexican American Generation' (1930-1960). A professor of education at the University of Texas from the beginning of World War II until the early 1970s, Sánchez was an outspoken proponent of integration and assimilation. He spent his life combating racial prejudice while working with such organizations as the ACLU and LULAC in the fight to improve educational and political opportunities for Mexican Americans. Yet his fervor was not always appreciated by those for whom he advocated, and some of his more unpopular stands made him a polarizing figure within the Latino community. Carlos Blanton has published the first biography of this complex man of notable contradictions. The author honors Sánchez's efforts, hitherto mostly unrecognized, in the struggle for equal opportunity, while not shying away from his subject's personal faults and foibles. The result is a long-overdue portrait of a towering figure in mid-twentieth-century America and the all-important cause to which he dedicated his life: Mexican American integration"--